2009
DOI: 10.1590/s0004-28032009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence rates of inflammatory bowel diseases, in midwestern of São Paulo State, Brazil

Abstract: -Context -The incidence and populational prevalence of inflammatory bowel diseases, hitherto unknown in Brazil, were estimated for a region in the Midwest of São Paulo State, Brazil. Methods -Using a sequential registry of 115 adult patients (>15 years old) with inflammatory bowel diseases -exclusively residing in the studied region with 533,508 inhabitants (2005) and attended at the reference hospital during a 20 year interval (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
102
4
47

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 19 publications
15
102
4
47
Order By: Relevance
“…Estudio realizado en San Pablo encontró estimativa de 14,8 casos por 100.000 habitantes, con igual proporción en relación a la incidencia entre mujeres y hombres (5) . En Piauí existen pocas investigaciones publicadas sobre ese tema, a pesar del creciente interés.…”
Section: Nº 47 Julio 2017unclassified
“…Estudio realizado en San Pablo encontró estimativa de 14,8 casos por 100.000 habitantes, con igual proporción en relación a la incidencia entre mujeres y hombres (5) . En Piauí existen pocas investigaciones publicadas sobre ese tema, a pesar del creciente interés.…”
Section: Nº 47 Julio 2017unclassified
“…1 An estimate of the prevalence in the city of São Paulo, Brazil, reported the occurrence of 14.8 cases per 100,000 inhabitants. 2 Protein-calorie malnutrition (PCM) has been reported in about 20 to 92% of patients with CD. [3][4][5][6][7] Many factors contribute to PCM and deficiency of macro-nutrients, vitamins and minerals in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of UC, the incidence in that country ranges between 9 and 12, with a prevalence of 205 to 240 per 100,000 inhabitants (15,17,22) . Studies have shown higher rates of incidence of IBD in developing countries, including Brazil (8,34,38) .…”
Section: Introductionmentioning
confidence: 99%